2008
DOI: 10.1107/s174430910706770x
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for the binding of naproxen to human serum albumin in the presence of fatty acids and the GA module

Abstract: The previously determined crystal structure of the bacterial albumin‐binding GA module in complex with human serum albumin (HSA) suggested the possibility of utilizing the complex in the study of ligand binding to HSA. As a continuation of these studies, the crystal structure of the HSA–GA complex with the drug molecule naproxen and the fatty acid decanoate bound to HSA has been determined to a resolution of 2.5 Å. In terms of drug binding, the structure suggests that the binding of decanoate to the albumin mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(56 citation statements)
references
References 25 publications
2
54
0
Order By: Relevance
“…In our experience cooling to 100K usually resulted in significant degradation of the order of the crystal lattice that increased mosaic spread and reduced the useful resolution of the data. Progress in this area has been made elsewhere and there are now several reports of HSA structures determined using data collected from cryo-cooled crystals, 12,28,30,31) though unfortunately some published reports lack an account of how cryo-cooling was achieved. 12,28) In contrast, Lejon and colleagues describe the use of either mineral oil or addition of 20% glycerol to the crystal harvest buffer to achieve cryo-cooling that permitted the determination of high-resolution structures (2.5-2.7°A) of complexes of HSA with a small domain from a bacterial surface protein.…”
Section: Methods For Crystallographic Analysis Of Serum Albuminmentioning
confidence: 96%
See 2 more Smart Citations
“…In our experience cooling to 100K usually resulted in significant degradation of the order of the crystal lattice that increased mosaic spread and reduced the useful resolution of the data. Progress in this area has been made elsewhere and there are now several reports of HSA structures determined using data collected from cryo-cooled crystals, 12,28,30,31) though unfortunately some published reports lack an account of how cryo-cooling was achieved. 12,28) In contrast, Lejon and colleagues describe the use of either mineral oil or addition of 20% glycerol to the crystal harvest buffer to achieve cryo-cooling that permitted the determination of high-resolution structures (2.5-2.7°A) of complexes of HSA with a small domain from a bacterial surface protein.…”
Section: Methods For Crystallographic Analysis Of Serum Albuminmentioning
confidence: 96%
“…12,28) In contrast, Lejon and colleagues describe the use of either mineral oil or addition of 20% glycerol to the crystal harvest buffer to achieve cryo-cooling that permitted the determination of high-resolution structures (2.5-2.7°A) of complexes of HSA with a small domain from a bacterial surface protein. 30,31) Elsewhere, 10-15% ethylene glycol has also been used as a cryo-protectant for crystals of defatted HSA grown from PEG 6000 (Kim L. Hein, Jesper V. Møller, Ulrich Kragh-Hansen, and Poul Nissen, unpublished data). In both cases the crystals were flash cooled in liquid nitrogen after incubation in the cryo-buffer.…”
Section: Methods For Crystallographic Analysis Of Serum Albuminmentioning
confidence: 98%
See 1 more Smart Citation
“…Protein crystals are usually frozen with mother liquor containing some cryoprotectants, typically 20% glycerol or ethylene glycol. 18,19 However, these typical cryoprotectant cannot be used for HSA. We have discovered a proper cryoprotectant (5-10% DMSO) to cryo-cool HSA crystals.…”
Section: Introductionmentioning
confidence: 99%
“…A combination of crystal packing and low-affinity binding of lidocaine may explain why an asymmetric 2:1 HSA:lidocaine complex has occurred. An examination of the literature (Carter and Ho, 1994;Sugio et al, 1999;Ghuman et al, 2005;Lejon et al, 2008;Zunszain et al, 2008;Zhu et al, 2008) revealed that so far no other HSA crystal has been reported to belong to this type of space group. The structure was determined by molecular replacement and refined at 3.3 Å resolution.…”
Section: Structure Of the Hsa-lidocaine Complex And Of Hsa With Sulphatementioning
confidence: 95%